Consanguinity-related hyperdontia: An orthopantomographic study - Shereen M Shokry; Mohammed S Alenazy (Dental Research Journal, 2013)
Background: The aim of this retrospective study was to describe the distribution of the non-syndromal supernumerary teeth (NSST) in a population of patients who attended the clinics of Riyadh Colleges of Dentistry and Pharmacy (RCsDP), Riyadh, Saudi Arabia. Materials and Methods: The study reviewed 1521 panoramic radiographs of Saudi and non-Saudi subjects who attended RCsDP clinic from November 2009 to November 2010. The data were analyzed using the Statistical Package for Social Sciences, utilizing Chi-square. Results: Eighteen (1.2%) patients were found to have NSST, comprising twelve males (66.7%), and six females (33.3%). The most common supernumerary teeth (ST) were the pre-molars six cases (33.3%), followed by the mesiodens, five cases (27.8%). The canines and distomolars three cases (16.6%) each respectively, while the least were the lateral incisors and paramolars of the two cases (11.1%) each. Conclusion: Consanguinity appeared to have a role in the development of hyperdontia in Saudi population because 13 cases (72.2%) out of 18 cases had consanguineous parents, while all patients having consanguineous parents had eumorphic ST.